Early summer warming amplification threats towards sustainable development goals (SDGs) in India - Susanta Mahato; Swades Pal; P.K. Joshi; Andreas Matzarakis; Paolo Tarolli; Vicky Anand (Ecological Informatics)
This study investigates the anomalous surge in early summer Land Surface Temperature (LST) in India and its potential repercussions on various sectors, such as food security, energy resources, and public health. The research also assesses the implications of the accomplishment of the Sustainable Development Goals (SDGs) throughout the early summer. Analyzing data from 2001 to 2022, the findings reveal that early summer LST was notably increased, with daytime temperatures exceeding mean LST by 3.5–4.14 °C and nighttime temperatures by 0.83 to 2.41 °C. Anomalous positive Standard Anomaly (StA) deviations were prevalent in north-west, central northeast, west-central, and hilly regions during the day. Trend analysis indicated varying StA responses across six homogeneous monsoon regions, with an overall positive trend observed in most areas. Surprisingly, Sea Surface Temperature (SST), which typically influences summer heating, was not the primary driver in 2022. Instead, a prolonged rain deficit in significant parts of India was identified as the cause. Regression analysis between StA and crop yields showed statistically insignificant associations for most production regions, except for a detrimental impact on winter crop yields. Energy deficits of up to 15 % were recorded in heat-affected states. The study also considered potential health issues arising from summer warming. These cumulative effects pose significant challenges to India's economic growth. The study assesses mitigation strategies discussed at the COP27 summit to address early summer warming. The findings provide valuable insights for developing preparedness and resilience plans to mitigate these issues.